Pengaruh Pemberian Pakan Fermentasi Terhadap Pertumbuhan dan Kelangsungan Hidup Ikan Lele (Clarias sp.) - Yohanna Lumban Tobing; Syammaun Usman (AQUACOASTMARINE, 2018)
Catfish beeding is mostly done by using intensive system. The rate of fish growth is strongly influenced by the type and quality of feed given and environmental conditions. If there are sufficient good quality feed given and suppated enviroment, it can be ascertained assured that fish of growth to will be fast. This research was done in UPTD. Tuntungan Fish Seed House in April to Mei 2018, which aims to determine the effect of fermented feed on the growth and survival of catfish. The study used Completely Randomized Design (RAL) with 3 treatment and 3 replications, as follows: V1 (viterna 20 ml / kg), V2 (viterna 40 ml / kg) and V3 (viterna 60 ml / kg). The data were analyzed by using Analysis of Variance (ANOVA), if there is any effect of treatment continued with the test of the Smallest Real Difference (BNT). As the result the most effective dose is 40 ml/kg. The research shows that the fermentation of feeds has different effect on the real growth but does not significantly affect the survival of the catfish.Keywords: Catfish (Clarias sp.), Viterna Probiotics Feeding Frequency, Growth